Bright solitons in bose–einstein condensates with field-induced dipole moments - Abdullaev, Fatkhulla Kh.; Gammal, Arnaldo; Malome, Boris A.; Tomio, Lauro (Institute of Physics Publishing (IOP), 2014)
We introduce an effectively one-dimensional model of a bosonic gas of particles carrying collinear dipole moments which are induced by an external polarizing field with the strength periodically modulated along the coordinate, which gives rise to an effective nonlocal nonlinear lattice in the condensate. The existence, shape and stability of bright solitons, appearing in this model, are investigated by means of the variational approximation and numerical methods. The mobility of solitons and interactions between them are studied too.